Development of a Model for Measuring the Quality of Corporate Governance in Insurance Groups in the Context of Cross-Border Operations - Kovačič, Saša; Jovanović, Dušan (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Insurance companies play a systemic role in capital allocation and sustainable risk management, making corporate governance quality crucial for financial stability. This study develops a comparative Corporate Governance Index (CGI) for insurers, positioning ESG as its central analytical pillar. The model is structured around five dimensions: board composition and functioning, transparency and disclosure, shareholder rights, ESG integration, and the organisation of key functions under Solvency II. Using panel data for 2014–2024 covering insurers in Slovenia and selected South-East European countries, with particular focus on the Triglav and Sava Re groups, the research applies correlation and multivariate regression analysis to test the relationship between CGI values, ESG integration, company size, and market development. The findings conceptualise ESG as a structural determinant of governance quality rather than merely a reporting practice and offer a practical analytical tool for regulators and corporate decision-makers.